The STANDARDIZATION OF A TRADITIONAL POLYHERBAL FORMULATION WITH PHARMACOGNOSTIC STUDY; ITS PHYTOCHEMICAL CONTENT, ANTIOXIDANT, AND ANTIDIABETIC ACTIVITY - ARUNIKA SUBBA; PALASH MANDAL; Subba, Arunika (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Pharmacognostic study, evaluation of antioxidant and antidiabetic activity along with phytochemical contents of an ethnomedicine (AR) which is used for the treatment of arthritis and diabetes in some villages of West Sikkim. Methods: The herbal formulation was extracted in a Soxhlet apparatus successively in ten solvents from low to high polarity. The extracts were subjected to antioxidant activity, qualitative and quantitative phytochemical estimation as well as in vitro antidiabetic activity. For pharmacognostic characterization, parameters such as fluorescence activity, physicochemical values, powder microscopy, and thin-layer chromatography (TLC) were performed. Mean values with p<0.05 were considered significant in statistical analysis. Results: Pharmacognostic study revealed various plants tissues. Ash values suggested the presence of earthy materials and moisture content near to the maximum range. Variation of colors was exhibited by AR in fluorescence analysis. TLC expressed the presence of phytoconstituents and the Rf values were noted down to be used in the future for authentication of the sample. Potential antioxidant capacity was observed in AR, phenolics significantly contributing in 1,1-diphenyl-2-picrylhydrazyl scavenging activity, 2, 2’-azinobis (3-ethylbenzothiazoline-6-sulfonic acid)+ scavenging activity and reducing power. Non-polar solvent showed the presence of alkaloid and steroids. The antidiabetic activity was very high in some extracts of AR with acetone extract showing the highest enzyme inhibiting activity. IC50 of acetone extract was 0.26±0.003 mg/ml. Conclusion: Overall study established a basic reference for the formulation AR. It was considered to possess antioxidant activity, but the interesting part of the study was its antidiabetic activity which is needed to be validated with in vivo studies and toxicity assessment.